Moral harassment. Types, characteristics and risk factors in the organizational context - Castro-Ospino, Naik C. (2020)
The research analyzed the mobbing in the organizational context from the discipline of counseling. It was held at the administrative headquarters of a supermarket / department store chain in the city of Maracaibo. It was a descriptive, field study with a non-experimental, transactional design. The population was census, made up of 43 employees. A questionnaire validated by expert judgment was used with a reliability index according to the Cronbach's alpha Coefficient of 0.853. The results do not show a high percentage of behaviors that constitute mobbing and when it occurs, the author of the mobbing is mainly the supervisor. The profile to the personality´s characteristics that favor situations of the Mobbing, it is located in the middle category for the stalker and low for the stalked. Regarding the factors that generate risk of mobbing, the absence of interest, support and relationship with supervisors is in a high category. The strategies to face the mobbing are in the middle category, except for the confrontation that was in the low category. It is concluded that the mobbing is a phenomenon that psychologically damages to the employee and affects the integrity of the worker.